P.016 Reduction in migraine-associated burden over 24 weeks of treatment with eptinezumab in patients with chronic migraine. (June 2022) - McAllister, P; Kudrow, D; Cady, R; Hirman, J; Ettrup, A; Minhas, S
Abstract : Background: To examine changes in the occurrence, severity, and symptoms of headache episodes in patients with chronic migraine (CM) following eptinezumab treatment. Methods: PROMISE-2 (NCT02974153) was a double-blind, placebo-controlled, parallel-group trial that randomized adults with CM to eptinezumab 100 mg, 300 mg, or placebo IV every 12 weeks for up to 24 weeks (2 infusions). Headache episodes (migraine and non-migraine) and their characteristics were reported in daily electronic diaries during the 28-day baseline period and throughout the 24-week treatment period. Results: A total of 1072 patients were included. Patients reported a mean of 20.4–20.6 monthly headache days during baseline across treatment groups. Mean monthly headache days decreased by 8.9 (100 mg) and 9.7 (300 mg) with eptinezumab versus 7.3 with placebo over weeks 1-24. Mean monthly headache episodes also decreased by 8.4 (100 mg) and 9.0 (300 mg) compared to 7.1 with placebo over weeks 1-24. Among headaches occurring post-treatment, decreases in severe pain, nausea, phonophobia, photophobia, and physical activity limitations were numerically greater than placebo. Conclusions: In patients with CM, eptinezumab numerically decreased the frequency and severity of monthly headache days and episodes more than placebo. Patients treated with eptinezumab reported a decrease in burdensome symptoms of headache episodes.